The definitive guide to PC-BSD - Lavigne, Dru. ([New York, N.Y.] : Apress ; New York, NY : Distributed to the book trade worldwide by Springer-Verlag, 2010)
In a thorough reference for both beginning and advanced users of PC-BSD--a free, easy-to-use operating system that is fast becoming a hassle-free alternative to Linux--teaches how to contribute one's prowess to the global PC-BSD community.
Includes index.
Keywords: Berkeley BSD (Computer file); Operating systems (Computers)